2013
DOI: 10.4103/2319-4170.110401
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Pelvic Fractures Associated with Femoral Shaft Fractures: A Retrospective Analysis

Abstract: Stabilization of the hemodynamics in patients with combined fractures should be the first aim. Angiography to stop arterial bleeding in the pelvis is often life-saving. The definitive treatment for combined fractures, such as pelvic fractures and femoral shaft fractures, should wait until hemodynamics is stabilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…One of them was in the case of a urinary tract injury, 1 in the case of symphyseal separation, and 1 in a comminuted rami fracture for a shortening operation time. Other studies use ramus screws (antegrade or retrograde) when possible (10). There was no complication from external fixators.…”
Section: Discussionmentioning
confidence: 98%
“…One of them was in the case of a urinary tract injury, 1 in the case of symphyseal separation, and 1 in a comminuted rami fracture for a shortening operation time. Other studies use ramus screws (antegrade or retrograde) when possible (10). There was no complication from external fixators.…”
Section: Discussionmentioning
confidence: 98%
“…Floating hip injuries are most often caused by highenergy trauma, such as a high-energy automotive or motorcycle (2,3,5,21). Cases due to falls from height have also been reported (3,12).…”
Section: Etiologymentioning
confidence: 99%
“…Cech et al reported a mortality rate of approximately 3% for floating hip injury in their population (4). In particular, floating hip injury involving pelvic ring fracture has a higher mortality EFORT Open Reviews (2024) 9 150-159 https://doi.org/10.1530/EOR-23-0013 Hip rate (3,5) and tends to occur in the initial phase of treatment (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are often caused by high-energy trauma and are associated with a high mortality rate. 1 However, such severe injuries with complex patterns are seen more commonly nowadays due to high-speed trauma caused in road traffic accidents (RTA) on motorways. High mortality rates (50%–77%) have been reported for femoral shaft fractures associated with pelvic fractures and injuries to other systems.…”
Section: Introductionmentioning
confidence: 99%